ENHANCING ELDERLY KNOWLEDGE THROUGH HEALTH EDUCATION ON HYPERTENSION AT TAMAN VILLAGE HALL SIDOARJO - Sulistyowati, S.Kep., M.Kes, Agus; Prasetyo Wijayanti, Dini; Puji Listari, Risti; Hadi Lara, Prianessa (Community Service Journal of Indonesia, 2025)
Taman village in  Sidoarjo is a developing village; however, many of its elderly residents still lack awareness regarding the importance of health knowledge, especially about hypertension. Many elderly individuals do not understand how to recognize symptoms, risk factors, or prevention efforts. This situation is worsened by misinformation obtained from unreliable sources. Families and community leaders often do not prioritize health education, causing essential hypertension-related information to be poorly delivered. This community service program was conducted at Taman Village Hall during a community meeting. The aim of this activity was to enhance elderly knowledge about hypertension and encourage preventive behavior such as maintaining a healthy diet, reducing salt intake, and regularly monitoring blood pressure. The activity was carried out through direct health education using leaflets and visual aids. The stages included: (1) Pre-test to assess baseline knowledge; (2) Material presentation on hypertension; (3) Discussion and Q&A session; (4) Post-test to evaluate knowledge improvement; and (5) Monitoring and evaluation. A total of 50 participants joined the program, although not all were elderly. Expected outcomes include the completion of a publishable article and the development of educational leaflets that can be proposed for intellectual property rights.